HISTORY OF CLASSIC THERMODYNAMICS AND THE FUTURE OF THERMODYNAMICS - Avsec, Jurij; Novosel , Urška (Journal of Energy Technology, 2024)
Whenever they hear the word “thermodynamics”, many students of energy engineering, mechanical engineering, chemistry, physics and other natural sciences are filled with apprehension. This science has a reputation because of its abstract nature and the laws of thermodynamics. This review paper deals with the history of thermodynamics and shows how it is likely to evolve in the future.